2B.01: IRON OVERLOAD EXERTS SYMPATHOEXCITATORY EFFECTS IN MEN WITH ESSENTIAL HYPERTENSION. (June 2015) - Seravalle, G.; Trevano, F. Quarti; Boggioni, I.; Buzzi, S.; Mancia, G.; Grassi, G.
Abstract : Objective: A recent hypothesis claims that iron metabolism directly or indirectly, i.e. throughout metabolic (insulin resistance) or inflammatory/autoimmune mechanisms, may be linked to the sympathetic nervous system. In the present study we tested this hypothesis by recording central sympathetic neural outflow in hypertensive patients characterized by normal or elevated circulating plasma levels of ferritin (FE), i.e. a marker of iron load. Design and method: In 8 untreated male essential hypertensives with elevated plasma FE (HTFE+, age 46.9 ± 2.6 yrs, mean ± SEM), we measured, along with Fe levels and transferrin saturation, body mass index clinic blood pressure (BP), heart rate (HR, EKG), muscle sympathetic nerve traffic (MSNA, microneurography), HOMA index, glucose, tryglicerides and cholesterol levels. Data were compared to those from 7 untreated male essential hypertensive patients with normal FE levels (HTFE-) age matched with HTFE+. Results: For similar BP, HR and BMI values, HTFE+ displayed FE values significantly greater than those seen in HTFE- (444.3 ± 101 vs 135.4 ± 98 μg/l, p < 0.05). This was the case also for transferrin saturation (38.9 ± 24 vs 24.2 ± 9.9 %). IN HTFE+ the increased iron load was accompanied by slightly, although not significantly, greater glucose, cholesterol and triglyceride plasma levels. More importantly, HOMA index values were significantly greater in HTFE+ than HTFE- (2.1 ± 0.4 vs 1.2 ± 0.2 au, P < 0.05). This was accompanied by significantly greater values of MSNA, both when expressed as bursts frequency over time (48.5 ± 4.3 vs 39.7 ± 3.5, <0.05) and when corrected for HR (66.4 ± 5.0 vs 50.9 ± 4.4, P < 0.05). In the group as a whole there was a significant relationship between MSNA and FE (r = 0.64, P < 0.01) whose level of significance was greater than the one related to the relationship MSNA and HOMA index (r = 0.53, P < 0.05). HOMA index and FE were also significantly and directly related each other (r = 0.56, P < 0.05). Conclusions: These data provide the first evidence that in hypertensive males iron overload exerts marked sympathoexcitatory effects associated with a decrease in insulin sensitivity. It is likely that the iron overload directly or throughout the concomitant hyperinsulinemia may be responsible for this neuroadrenergic response.